Natural Resources: An Incentive or an Obstacle to Economic Growth? - Rica Ivan; Calin Tanase Ladar (Agora International Journal of Economical Sciences (AIJES), 2018)
This paper refers to the consequences of the presence of natural resources for countries endowed with such resources and the impact of such resources on their economy. It briefly describes the experience of some of these countries, presenting the success of those who benefited from these resources and the monetary, fiscal and exchange rate related aspects thereof. The concept of annuity initially refers to the remuneration related to ownership rights upon a limited resource. The paper provides an overview of situations that can influence the relation between natural resources, economic growth and some of the related key factors.
Keywords: 330